Thermodynamic Analysis of Nuclear Power Plants with External Steam Superheating - Vladimir Kindra; Mikhail Ostrovsky; Igor Maksimov; Roman Zuikin; Nikolay Rogalev (Energies)
Increasing the efficiency and capacity of nuclear power units is a promising direction for the development of power generation systems. Unlike thermal power plants, nuclear power plants operate at relatively low temperatures of the steam working fluid. Due to this, the thermodynamic efficiency of such schemes remains relatively low today. The temperature of steam and the efficiency of nuclear power units can be increased by integrating external superheating of the working fluid into the schemes of steam turbine plants. This paper presents the results of a thermodynamic analysis of thermal schemes of NPPs integrated with hydrocarbon-fueled plants. Schemes with a remote combustion chamber, a boiler unit and a gas turbine plant are considered. It has been established that superheating fresh steam after the steam generator is an effective superheating solution due to the utilization of heat from the exhaust gases of the GTU using an afterburner. Furthermore, there is a partial replacement of high- and low-pressure heaters in the regeneration system, with gas heaters for condensate and steam superheating after the steam generator for water-cooled and liquid-metal reactor types. An increase in the net efficiency of the hybrid NPP is observed by 8.49 and 5.11%, respectively, while the net electric power increases by 93.3 and 76.7%.